2009
DOI: 10.1016/j.bmc.2008.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the mechanism of a tight binding inhibitor of AIR carboxylase

Abstract: The enzyme aminoimidazole ribonucleotide (AIR) carboxylase catalyzes the synthesis of the purine intermediate, 4-carboxy-5-aminoimidazole ribonucleotide (CAIR). Previously, we have shown that the compound 4-nitro-5-aminoimidazole ribonucleotide (NAIR) is a slow, tight binding inhibitor of the enzyme with a K i of 0.34 nM. The structural attributes and the slow, tight binding characteristics of NAIR implicated this compound as a transition state or reactive intermediate analog. However, it is unclear what molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…In drug discovery replacement of canonical nucleobases [5] by substituted five-membered heterocyclic rings such as imidazole or triazole has been particularly successful. Ribavirin [6e12], AICA [13,14], Bredinin [15,16] and TSAO analogues [17,18] are the best known examples among these analogues (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In drug discovery replacement of canonical nucleobases [5] by substituted five-membered heterocyclic rings such as imidazole or triazole has been particularly successful. Ribavirin [6e12], AICA [13,14], Bredinin [15,16] and TSAO analogues [17,18] are the best known examples among these analogues (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…16 The resulting inosine acetonide 2′ (not shown) was chromatographed to obtain 2′ free of buffer salts and enzyme in 69% yield over two steps. In the carbon-13 labeled case, commercially available 1 was subjected to adenosine deaminase enzyme to cleanly form [ 13 C 5 -ribose] inosine 2.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] An acetonide protecting group was then installed as previous reports have indicated that phosphorylation of a similar ribose 5′-hydroxyl in the presence of unblocked 2′-and 3′-hydroxyls is not completely selective. 16 The resulting inosine acetonide 2′ (not shown) was chromatographed to obtain 2′ free of buffer salts and enzyme in 69% yield over two steps. 17,18 Subsequent acetylation afforded compound 3 in 94% yield that was used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…3 The architecture of the active sites of bacterial PurE and the PurE domain in hPur6 are nearly superimposable, and yet despite these conserved features, biochemical studies have shown that both enzymes are highly specific. 4 Subsequent studies have shown that bacterial PurE has the potential to be a target for new antibiotic development. 5 In this study, a fluorescence-based 6 thermal shift assay 7,8 was applied to B. anthracis PurE (BaPurE) for high-throughput screening (HTS) to identify molecules (hits) that bind to BaPurE.…”
Section: Introductionmentioning
confidence: 99%